“You Dare to Compare Yourself to Shakespeare?”: Philip Roth, American Bard - Simonetti, Paolo (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2021)
Philip Roth’s writing has been consistently inspired and influenced by Shakespeare’s theater on multiple levels. This essay aims to investigate Roth’s Shakespearean imagination by tracing the evolution of characters, themes, symbolism, and motifs derived from the Bard’s plays, focusing in particular on Operation Shylock and Sabbath’s Theater. Throughout his career, Roth’s negotiations with Shakespeare were often antagonistic and competitive, but, as time passed, allusions to the Bard in his novels became more accurate, while Roth’s writing took on a strong performative vein. In his most accomplished works, Roth ‘invented’ (or reinvented) the character of “the author” – the writer, the playwright, the artist – and set a pseudo-autobiographic alter-ego on the stage of contemporary America. For a writer who continually performed the character of “the author” in his texts as well as outside (in interviews, essays etc.), it is only natural to model his public persona on the English playwright, eventually impersonating the role of “American bard”.